Keputusan Struktur Modal dan Kebijakan Dividen sebagai Mekanisme Mengurangi Masalah Keagenan - Yulianto, Arief (JDM (Jurnal Dinamika Manajemen), 2013)
The managerial opportunistic behaviour on the financing activity decision can generate a conflict between the management and the stockholder or creditor as a consequence of the opportunity management behaviors. This paper aims to provide empirical evidence on the managerial ownership (agency costs hypothesis) which suggests debt equity ratio and dividend payout ratio may reduce agency costs. This research was conducted at manufacturing firms listed at Indonesian Stock Exchange from 2008 to 2011. In this research, two regression models were used. Management ownership is positively associated with debt equity ratio. It indicates that the increase of monitoring, done by creditors, due to the increasing amount of debt. However, there is not a significant relationship between management ownership and dividend payout ratio, it indicates that the finding is inconsistent with the agency conflict.